Scalable Platform for Nanocrystal‐Based Quantum Electronics. (21st April 2022) - Sestoft, Joachim E.; Gejl, Aske N.; Kanne, Thomas; Schlosser, Rasmus D.; Ross, Daniel; Kjær, Daniel; Grove‐Rasmussen, Kasper; Nygård, Jesper
Abstract: Unlocking the full potential of nanocrystals in electronic devices requires scalable and deterministic manufacturing techniques. A platform offering compelling paths to scalable production is microtomy, the technique of cutting thin lamellas with large areas containing embedded nanostructures. So far, this platform has not been used for the fabrication of electronic quantum devices. Here, microtomy is combined with vapor–liquid–solid growth of III/V nanowires to create a scalable platform that can deterministically transfer large arrays of single and fused nanocrystals—offering single unit control and free choice of the target substrate. Electronic devices are fabricated on cross‐sectioned InAs nanowires with good yield, and their ability to exhibit quantum phenomena such as conductance quantization, single‐electron charging, and wave interference are demonstrated. Finally, it is devised how the platform can host rationally designed semiconductor/superconductor networks relevant to emerging quantum technologies. Abstract : An innovative platform combining microtomy with newly developed nanowire network growth techniques is presented. It enables large‐scale transfer and deterministic placement of high‐quality nanocrystals and networks to almost any substrate. Individual nanocrystals exhibit excellent field effect mobilities and quantum transport phenomena, showing the potential of the platform for large‐scale architectures of quantum devices.